2021
DOI: 10.1159/000518318
|View full text |Cite
|
Sign up to set email alerts
|

Germline VHL Mutation Discovered in Association with EGFR-Positive Lung Cancer and Metachronous Hepatocellular Carcinoma: A Case Report

Abstract: VHL is a tumor suppressor gene located on chromosome 3 that is classically associated with tumors of the eye and CNS, renal cell carcinoma, and pheochromocytoma. We describe what appears to be the first report of an association between a germline VHL mutation and non-small cell lung cancer and metachronous hepatocellular carcinoma (HCC). Our case involves a 63-year-old nonsmoking male who was initially diagnosed with EGFR mutation-positive metastatic nonsquamous, non-small cell lung adenocarcinoma, who subsequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 14 publications
1
0
0
Order By: Relevance
“…In particular, it is important for the clinician to be aware of diseases such as VHL that have risk for additional tumors not only in the individual but also in family members as in this case where the patient's diagnosis led to examination and diagnosis of VHL in the patient's mother and aunt. This is similar to work by Kuhlman et al [ 7 ] who found an incidental diagnosis of VHL in a patient who presented with both lung cancer and hepatocellular carcinoma. RCH is often the first presenting sign of a diagnosis of VHL, and one must be aware of the systemic implications [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…In particular, it is important for the clinician to be aware of diseases such as VHL that have risk for additional tumors not only in the individual but also in family members as in this case where the patient's diagnosis led to examination and diagnosis of VHL in the patient's mother and aunt. This is similar to work by Kuhlman et al [ 7 ] who found an incidental diagnosis of VHL in a patient who presented with both lung cancer and hepatocellular carcinoma. RCH is often the first presenting sign of a diagnosis of VHL, and one must be aware of the systemic implications [ 8 ].…”
Section: Discussionsupporting
confidence: 91%